Cellular and Molecular Changes in Orthodontic Tooth Movement - Shahrul Hisham Zainal Ariffin; Zulham Yamamoto; lntan Zarina Zainol Abidin; Rohaya Megat Abdul Wahab; Zaidah Zainal Ariffin (The Scientific World Journal)
Tooth movement induced by orthodontic treatment can cause sequential reactions involving the periodontal tissue and alveolar bone, resulting in the release of numerous substances from the dental tissues and surrounding structures. To better understand the biological processes involved in orthodontic treatment, improve treatment, and reduce adverse side effects, several of these substances have been proposed as biomarkers. Potential biological markers can be collected from different tissue samples, and suitable sampling is important to accurately reflect biological processes. This paper covers the tissue changes that are involved during orthodontic tooth movement such as at compression region (involving osteoblasts), tension region (involving osteoclasts), dental root, and pulp tissues. Besides, the involvement of stem cells and their development towards osteoblasts and osteoclasts during orthodontic treatment have also been explained. Several possible biomarkers representing these biological changes during specific phenomenon, that is, bone remodelling (formation and resorption), inflammation, and root resorption have also been proposed. The knowledge of these biomarkers could be used in accelerating orthodontic treatment.